Problématisation de situations interculturelles en master « Métiers de l’éducation et de la formation » - Véronique Lemoine-Bresson; Virginie Trémion (Recherches en Éducation)
The article shows how two cohorts of students in a Master's degree in Education and Training at a College of Education problematize an intercultural situation when viewing the video called What kind of Asian are you? For students, problematization is difficult to achieve when it comes to questioning their own value judgments. We question their ways of identifying observables to establish the problem that arises in a staged intercultural situation. After presenting the theoretical framework of our study and the methodological protocol, we discuss the results of our analyses. These results provide a fresh thinking on new practices for intercultural training based on a device that focuses on problematization.